Acta Historiae Neerlandicae/Studies on the History of the Netherlands VI - Brulez, W. author. aut Link
VIII, 220 p.
Keywords: The five previous volumes of the Acta Historiae Neerlandicae appeared under the auspices of the Netherlands Committee for Historical Sciences. When in 1970 this Committee merged with the Historical Society to form the Dutch Historical Society (Nederlands Historisch Genootschap) an opportunity arose to rethink the aims of the Acta's original promotors. Also this sixth and succeeding volumes became the responsibility of the new combined Society as above. The volumes will from now on be published at The Hague by Martinus Nijhoff. From the early days of the Acta language barriers were broken down, and interested scholars from other countries could acquaint themselves with deve lopments in historical work in the Low Countries hitherto published only in Dutch. The Acta thus enabled discussion on Dutch historical topics to become international. However, initially subjects covered a wide field, not only of Dutch but also of general history, and articles were translated from Dutch not only into English but also into French and German. If sales can be taken as a guide, it appeared that scholars were not finding in the Acta precisely what they were seeking. Editors' expectations, and therefore their hopes, were, it was felt, going unrealised.